Incompletely obliterated cranial arteriovenous fistulae are safely and effectively treated with adjuvant ε-aminocaproic acid. (11th October 2017) - Howard, Brian M; Grossberg, Jonathan A; Prater, Adam; Cawley, C Michael; Dion, Jacques E; Tong, Frank C
Abstract : Background: Administration of ε-aminocaproic acid (εACA), as adjuvant therapy following incompletely embolized cranial dural arteriovenous (dAVFs) and direct carotid artery to cavernous sinus fistulae (CCFs), is a strategy to promote post-procedural thrombosis. However, the efficacy of εACA to treat incompletely obliterated dAVFs and CCFs has not been published. The purpose of this study was to determine if administration of εACA following incomplete embolization of cranial dAVFs or CCFs was associated with an increased likelihood of cure on follow-up imaging compared with patients not given adjuvant εACA. Methods: A retrospective cohort study was performed. All patients who underwent treatment of a dAVF or CCF at our institution between 1998 and 2016 were reviewed (n=262). Patients with residual shunting following the first attempted endovascular embolization were included in the analysis (n=52). The study groups were those treated with εACA following incomplete obliteration of the fistula and those who were not. The primary outcome was obliteration of the fistula on initial follow-up imaging. Complication rates between cohorts were compared. Results: 20 (38%) patients with incompletely obliterated fistulae were treated with adjuvant εACA. A trend towards an improved rate of complete obliteration on initial follow-up imaging was observed in the group treated with εACA (55% vs 34% in the group not treated with εACA, p=0.14). No difference in clinical outcomes or thromboembolic complications was observed between the groups. Conclusions: In summary, these data suggest that administration of εACA is a safe adjuvant therapy in the management of cranial dAVFs and CCFs that are incompletely treated endovascularly.